RELATIONSHIP BETWEEN PULMONARY VASCULAR THICKENINGS WITH CT-SEVERITY SCORE IN COVID-19-CONFIRMED PATIENTS - Danu, Alex; Asriyani, Sri; Latief, Nikmatia; Alfian, Andi; Iskandar, Harun; Rauf, Rafikah (E-Jurnal Medika Udayana, 2024)
Introduction: Previous studies have shown pulmonary vascular thickening found in COVID- 19 patients. In addition, the CT-Severity Score (CT-SS) scoring system have become a reference in assessing the severity of COVID-19. This study analyzes the relationship between pulmonary vascular thickening on CT-Scan thorax with CT-SS in patients with confirmed COVID-19. Materials and Methods: A retrospective cross-sectional study was conducted on 137 patients with confirmed COVID-19 at the Radiology Installation of Doctor Wahidin Sudirohusodo Hospital Makassar. Patients who were eligible and had undergone a chest CT-Scan were then measured for their pulmonary vascular thickness in the intralesional and extralesional areas of the secondary lung lobes. The CT-SS score was assessed to determine the degree of mild or severe disease based on the opacity of the involved lung segment. Independent T-test and Chi- square were used to determine the differences and relationships between the variables studied. Results: Based on CT-SS, most subjects were classified as mildly ill (CT-SS < 19.5, 78/137 people). The mean intralesional and extralesional vascular thickening was 2.65 ± 0.48 and 2.17 ± 0.36, respectively. There was a significant difference between vascular thickness between subjects with mild and severe CT-SS categories (intralesion: 2.4 ± 0.33 vs. 2.99 ± 0.47, p=0.001; extralesion: 2.04 ± 0.28 vs. 2.35 ± 0.39), Conclusion: Vascular thickening on CT-Scan chest images is related to the severity of COVID-19 as measured by CT-SS scoring. Keywords: COVID-19, Chest CT-Scan, CT-Severity Score , Pulmonary Vascular Thickening